2020
DOI: 10.1002/bmc.5017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cattle poisoning by Bifenthrin via earwax analysis by HS/GC–MS

Abstract: The use of pyrethroids has increased over recent years, and corresponds to a higher exposure of animals to pesticide residues in the environment and diet. Here, an outbreak of pyrethroid poisoning in beef cattle was reported occurring in Midwestern Brazil. After veterinary evaluation, it was observed that the bovines presented common pyrethroid intoxication symptoms. Aiming to identify the cattle poising by pyrethroid, earwax samples were collected from two groups: exposed and nonexposed animals from the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recently, a number of reports have investigated other possible samples, including cerumen (earwax) [53][54][55][56]; bone [99,100]; adipocere, also known as corpse wax, grave wax or mortuary wax; brain tissue; flies; and pupae [58]. Meier et al reported the detection time window of cerumen, commonly referred as earwax, to be reportedly in excess of that of urine but shorter than that reported for hair [55].…”
Section: Cerumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of reports have investigated other possible samples, including cerumen (earwax) [53][54][55][56]; bone [99,100]; adipocere, also known as corpse wax, grave wax or mortuary wax; brain tissue; flies; and pupae [58]. Meier et al reported the detection time window of cerumen, commonly referred as earwax, to be reportedly in excess of that of urine but shorter than that reported for hair [55].…”
Section: Cerumenmentioning
confidence: 99%
“…The review covers recent advances in both GC and GC-MS applications applicable to the forensic discipline. The applications discussed include sweat and skin [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], cerumen [53][54][55][56], meconium [57][58][59], breast milk [60,61], larvae, pupae and insects [62][63][64][65], Vitreous humour [66][67][68][69][70][71], drug paraphernalia [72] cosmetics and fragrances [73][74][75][76][77][78], and air, gases and vapours [79][80][81][82][83][84]. A further section is dedicated to the application of pyrolysis GC-MS…”
Section: Introductionmentioning
confidence: 99%
“…It refers to secretions of the sebaceous and sweat glands containing polar and non-polar substances, mainly metabolic lipid-derived components. 16,17 Recently, cerumen VOMs have been successfully applied in diabetes diagnosis, 18,19 forensic applications, [20][21][22][23][24] toxicological monitoring purposes, [25][26][27][28][29] identification of rare otolaryngological disorder (Me ´nie `re's disease), 30 and human cancer diagnosis. 31 The chemical fingerprint of VOMs for use in disease detection is known as Cerumenogram.…”
Section: Introductionmentioning
confidence: 99%
“…Early instances of using cerumen to detect xenobiotics include its use for monitoring exposure, particularly in the long term, to organochloride pesticides and other persistent organic pollutants that tend to bioaccumulate in the human body [10, 11]. In a more recent application of pesticide determination, cerumen was collected from bovines to investigate symptoms consistent with pesticide poisoning, with bifenthrin being successfully detected [12]. Another animal study of a highly lipophilic substance investigated the pharmacokinetics of an anthelmintic drug, ivermectin, in swine, including an analysis of collected cerumen [13].…”
Section: Introductionmentioning
confidence: 99%